USING INTERACTIVE TECHNOLOGIES AND METHODS IN TEACHING BIOLOGY - Rahmatullayeva Anor Kayrullayevna (Modern American Journals, 2025)
Educational practice shows that the establishment of interdisciplinary connections in school education is a vivid expression of the integration processes taking place today in science and society. This connection plays an important role in the conscious assimilation of knowledge by students, the development of a holistic view of the world, and the improvement of their practical and scientific-methodical training. Such training allows graduates of general secondary education to freely apply the knowledge, skills, and competencies acquired in the classroom and in extracurricular activities, in production, and in general in any activity.
Keywords: Integration, science method, lesson, natural science, evrika, intellekt, kvest.